Determinants of Embryo Transfer Success in Tropical Dairy Cattle: Integrating Reproductive Performance and Institutional Factors - Mohamad Nurul; Abd. Rohman; Suherman (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2026)
Embryo transfer (ET) is an advanced reproductive biotechnology widely promoted to accelerate genetic improvement and productivity of dairy cattle. However, the success of ET programs in tropical smallholder systems remains inconsistent due to the interaction of biological, environmental, and institutional factors. This study aimed to identify the determinants of ET success by integrating reproductive performance analysis with institutional implementation assessment in tropical dairy production systems. A mixed-methods approach was used, combining quantitative analysis of 200 recipient dairy cows with qualitative interviews involving farmers, technicians, and livestock officials in Pasuruan Regency, East Java, Indonesia. Binary logistic regression was employed to evaluate the influence of embryo characteristics, recipient conditions, environmental stress, disease history, and technician experience on pregnancy outcomes. The results showed that pregnancy rates ranged between 20 and 50%, with fresh embryos achieving higher success than frozen embryos. Logistic regression analysis indicated that technician experience significantly increased the probability of pregnancy (OR = 1.236; p < 0.05), highlighting the critical role of technical capacity in ET implementation. Other factors, such as embryo quality, body condition score, parity, and heat stress, showed variable but statistically nonsignificant effects. Qualitative findings further revealed that limited technical human resources, inconsistent monitoring systems, and weak institutional coordination constrained program effectiveness. These findings demonstrate that ET success in tropical dairy systems is shaped not only by reproductive biology but also by institutional and managerial conditions. Strengthening technical capacity, improving reproductive management, and integrating ET programs into regional livestock innovation systems are essential to enhance the effectiveness and sustainability of reproductive biotechnology in developing dairy sectors.